The interactive weighted lap pad with emotional feedback / Ahmad Danial Hakim Rosman - Rosman, Ahmad Danial Hakim; Mohd Puad, Hedzween; Rosmaeini, Muhammad Harith Ikhwan; Abdullah, Azzaruddin; Mohd Noor Kamil, Nurin Izzati (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
We made this product to help people with disabilities ease their mind and make them be able to relax. We aim to make their mental health better and help their overall wellbeing with their better state of mind. This product will have important benefits that can help the disable and normal people. It can help perform better at work with a better state of mind. Its appeal lies in addressing the specific needs of individuals with disabilities or mental health challenges, offering a novel solution to manage symptoms and promote well-being. With scalable production capabilities and diverse applications across various settings, the product holds significant potential for market penetration and profitability.